1984
DOI: 10.1136/bmj.288.6419.751
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and ulcerative colitis.

Abstract: In several patients the findings that metastases were forming in some organs but not others, despite infusion of viable tumour cells into the systemic circulation, provides direct evidence supporting the "seed and soil" hypothesis of Paget." This proposes that although haematogenously released tumour cells (seeds) "are carried in all directions they can only live and grow" if they lodge in an organ (soil) that is congenial. The clearest demonstration of this was in the patient (case 12) who was known before in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(31 citation statements)
references
References 10 publications
2
28
0
1
Order By: Relevance
“…One survey provided new data and calculated that those patients who had never smoked had a much greater risk of developing ulcerative colitis than those who had previously smoked. 15 The reduced smoking by ulcerative colitis patients was consistent with the results of a mortality study which showed these patients, particularly men, had a reduced risk of circulatory and respiratory diseases and of cancer of the lung. 1 ,17 Further examination of these patients showed a lower systolic and diastolic blood pressure compared to matched controls 18 particularly in patients with extensive colitis and those who had undergone a panproctocolectomy.l9…”
supporting
confidence: 79%
See 1 more Smart Citation
“…One survey provided new data and calculated that those patients who had never smoked had a much greater risk of developing ulcerative colitis than those who had previously smoked. 15 The reduced smoking by ulcerative colitis patients was consistent with the results of a mortality study which showed these patients, particularly men, had a reduced risk of circulatory and respiratory diseases and of cancer of the lung. 1 ,17 Further examination of these patients showed a lower systolic and diastolic blood pressure compared to matched controls 18 particularly in patients with extensive colitis and those who had undergone a panproctocolectomy.l9…”
supporting
confidence: 79%
“…A further report, which reaffirmed the low prevalence of smokers among patients with ulcerative colitis, expressed the view that since cigarette smokers tended to do worse on most counts in health and welfare, all patients with inflammatory1' bowel disease should be advised to stop smoking.2 21 y2i A follow-up of a previous community-based stud made specific examination of the smoking habits of Crohn's disease patients 26,28 and found that they were significantly more likely to be smokers than ageand sex-matched controls, and that the association was stronger for smoking habit before the onset of disease rather than for current smoking habit. This prompted the concept that smoking could be an important determinant of the type of disease that develops in individuals predisposed to inflammatory bowel disease.2g Previous attempts at finding an environmental factor which had a link with Crohn's disease had found a consistent association with consumption of refined sugar.2g Cigarette smoking has also been linked with increased consumption of refined sugar.29…”
mentioning
confidence: 89%
“…The effect of smoking on the immune system as well as on the course of immunological diseases has been studied extensively but with conflicting results (18)(19)(20). Smoking influences both humoral (21) and cellular immunity (22) and has been suggested to have an immunosuppressive effect based on for example reports of a negative correlation between smoking and ulcerative colitis (23, 24)-a disease with a possible immunological etiology-with a clustering of disease onset after termination of smoking (25,26). This negative association was not seen in another autoimmune diseases, viz.…”
Section: Discussionmentioning
confidence: 97%
“…A 40% to 89% reduction in risk has been noted for current smokers compared with subjects who had never smoked (1)(2)(3)(4). Other information suggests that smoking after the onset of ulcerative colitis may have a therapeutic effect on this disease.…”
mentioning
confidence: 90%